Grain size effect on corrosion behavior of Inconel 625 film against molten MgCl2-NaCl-KCl salt. (1st April 2022) - Feng, Jinghua; Mao, Li; Yuan, Guangcui; Zhao, Youyang; Vidal, Judith; Liu, Li (Emily)
Abstract: This study evaluated the grain size effect of Inconel 625 film against molten chloride salt. It is found that larger grain size Inconel 625 exhibits better corrosion resistance by reducing Cr depletion. ~ 2 nm surface NiO layer of Inconel 625 is incapable of compensating the negative effects from more initiation corrosion sites. Mo is the least likely leached element and its enrichment occurs in Cr-depleted regions as a result of Mo diffusion. Mg and Cl are two most seen salt elements in all corroded samples, while K and Na only attack Inconel 625 with the smallest grain size. Highlights: Grain size of Inconel 625 films grows with rising deposition temperature. Larger grain size Inconel 625 possesses better corrosion performance. Cr depletion is alleviated by increasing the grain size. K and Na are only observed in the smallest grain size Inconel.